A randomized trial of an intervention to improve resident-fellow teaching interactions on the wards. Issue 1 (December 2016) - Gupta, Shruti; Alladina, Jehan; Heaton, Kevin; Miloslavsky, Eli
Abstract Background Subspecialty fellows can serve as a tremendous educational resource to residents; however, there are multiple barriers to an effective resident-fellow teaching interaction in the setting of inpatient consultation. We designed and evaluated a resident-directed intervention to enhance communication and teaching during consultation on the general medicine wards. Methods Five medical teams were randomized to receive the intervention over a 3 month period (3 control, 2 intervention teams). The intervention was evaluated with pre and post-intervention surveys. Results Fifty-nine of 112 interns completed the pre-intervention survey, and 58 completed the post-intervention survey (53 % response rate). At baseline, 83 % of the interns noted that they had in-person interactions with fellows less than 50 % of the time. 81 % responded that they received teaching from fellows in less than 50 % of consultations. Following the intervention, the percentage of interns who had an in-person interaction with fellows greater than 50 % of the time increased in the intervention group (9 % control versus 30 % intervention, p = 0.05). Additionally, interns in the intervention group reported receiving teaching in more than 50 % of their interactions more frequently (19 % control versus 42 % intervention, p = 0.05). There were no differences in other measures of teaching and communication. Conclusions We demonstrate that a time-efficient intervention increased perceptions of in-person communication and the number of teaching interactions between interns and fellows. Further studies are warranted to determine whether such an approach can impact resident learning and improve patient care.